Differential diagnosis of solitary gastric Peutz-Jeghers-type polyp with stomach cancer: a case report - Yoshizawa, Nao (Int J Surg Case Rep, 2018)
INTRODUCTION: Solitary Peutz-Jeghers-type polyps of the stomach are extremely rare. They are defined as unique polyps that are not associated with Peutz-Jeghers syndrome (PJS). PRESENTATION OF CASE: A 37-year-old woman presented at our hospital with anemia and epigastric discomfort. Esophagogastroduodenoscopy to determine the cause of anemia revealed a 5 × 6-cm pedunculated polypoid tumor at the greater curvature of the upper gastric body. Pathological examination of a biopsy specimen confirmed a Group 1 hyperplastic polyp. Computed tomography revealed neither lymph node swelling nor distant metastasis. A malignant component of the polypoid tumor was difficult to deny because of its size. The patient underwent local resection of the stomach. Her postoperative course was uneventful. A pathological examination of the surgical specimen revealed a Peutz-Jeghers-type, hamartomatous polyp containing an enlarged crypt with hyperplastic foveolar epithelium and smooth muscle proliferating into the lamina propria. No atypical cells were found in the overlying epithelium. Based on these findings, we performed colonoscopy and capsule endoscopy of the intestine. No polyps were found in the intestine or colon. She had no family history of any type of tumor and no mucocutaneous pigmentation. DISCUSSION: There were only 10 reports of solitary gastric Peutz-Jeghers polyps published to date. Although most of them did not have atypical cells, one case has proliferative component. A few reports have described relationship with malignant tumor. CONCLUSION: Solitary gastric PJ-type polyps are rare. Careful follow-up should be recommended and further studies are needed to evaluate cancer risk of solitary gastric PJ-type polyps.